Respuesta :

Answer:

the values of the non-integral roots of the polynomial equation are:

4.73 and 1.27.

Step-by-step explanation:

To find the roots of the polynomial equation, we need to factorize the equation:

x^4 − 4x^3 = 6x^2 − 12x ⇒ x^4 − 4x^3 -6x^2 +12x = 0

⇒ x(x+2)(x -3 + sqrt(3))(x -3 - sqrt(3))

Then, the non integral roots are:

x1 = 3 - sqrt(3) = 1.26 ≈ 1.27

x2 = 3 + sqrt(3) =  4.73

Then, the values of the non-integral roots of the polynomial equation are:

4.73 and 1.27

Answer:

The approximate values of the non-integral roots of the polynomial equation are:

                     1.27 and 4.73

Step-by-step explanation:

We are given an algebraic equation as:

[tex]x^4-4x^3=6x^2-12x[/tex]

i.e. it could be written as:

[tex]x^4-4x^3-6x^2+12x=0\\\\i.e.\\\\x(x^3-4x^2-6x+12)=0[/tex]

Since, we pulled out the like term i.e. "x" from each term.

Now we know that [tex]x=-2[/tex] is a root of the term:

[tex]x^3-4x^2-6x+12[/tex]

Hence, we split the term into factors as:

[tex]x^3-4x^2-6x+12=(x-2)(x^2-6x+6)[/tex]

Now, finally the equation could be given by:

[tex]x(x-2)(x^2-6x+6)=0[/tex]

Hence, we see that:

[tex]x=0,\ x-2=0\ and\ x^2-6x+6=0\\\\i.e.\\\\x=0,\ x=2\ and\ x^2-6x+6=0[/tex]

[tex]x=0\ and\ x=2[/tex] are integers roots.

Now, we find the roots with the help of quadratic equation:

[tex]x^2-6x+6=0[/tex]

( We know that the solution of the quadratic equation:

[tex]ax^2+bx+c=0[/tex] is given by:

[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex] )

Here we have:

[tex]a=1,\ b=-6\ and\ c=6[/tex]

Hence, the solution is:

[tex]x=\dfrac{-(-6)\pm \sqrt{(-b)^2-4\times 1\times 6}}{2\times 1}\\\\i.e.\\\\x=\dfrac{6\pm \sqrt{36-24}}{2}\\\\i.e.\\\\x=\dfrac{6\pm \sqrt{12}}{2}\\\\i.e.\\\\x=\dfrac{6}{2}\pm \dfrac{2\sqrt{3}}{2}\\\\i.e.\\\\x=3\pm 3\\\\i.e.\\\\x=3+\sqrt{3},\ x=3-\sqrt{3}[/tex]

Now, we put [tex]\sqrt{3}=1.732[/tex]

Hence, the approximate value of x is:

[tex]x=3+1.732,\ x=3-1.732\\\\i.e.\\\\x=4.732,\ x=1.268[/tex]